Inhibition of stress and spontaneous respiration: Efficacy and safety of monitored anesthesia care by target-controlled infusion remifentanil in combination with dexmedetomidine in fibreoptic bronchoscopy for patients with severe tracheal stenosis - Zhou, Yi; Wu, Wei; Zhu, Yuanjie; Lv, Xin; Liu, Jianming (Frontiers in Medicine, 2022)
Objective This study aimed to determine the effective concentration of target-controlled infusion (TCI) of remifentanil used to inhibit stress during the treatment of severe tracheal stenosis with fibreoptic bronchoscopy and to evaluate the monitored anaesthesia care (MAC) by remifentanil. Method 60 patients with severe tracheal stenosis who underwent fibreoptic bronchoscopy was performed. Dexmedetomidine was initially administered at a bolus dose (0.8 mcg/kg), followed by a 0.5 mcg/(kg·h) continuous infusion. Remifentanil was administered by TCI. The effective concentration (EC) of remifentanil was titrated by the improved sequential method, and 30 patients were included. The EC95 of remifentanil was set as the plasma target concentration to evaluate the safety of the MAC, and another 30 patients were included. Result The half effective effect-chamber concentration of remifentanil (EC50) was 2.243 ng/ml, and the EC95 was 2.710 ng/ml. Among the 30 patients who received an EC95 of remifentanil as the target concentration, 1 patient was remedied by injecting propofol, the score of Ramsay sedation was 3. The incidence of subclinical hypoxemia (SPO2 of 90-95%) was 30%, the incidence of moderate hypoxemia (SPO2 of 75-89%, ≤60 s) was 20%, and 86.7% of patients with oxygen saturation was less than 95% returned to normal by awakening. The satisfaction score of the operator was 9, the satisfaction score of the anaesthesiologist was 8, the satisfaction score of the patients was 10, the rate of patient willingness to re-accept the procedure was 93.3% and the circulation was stable during the operation. Conclusion MAC using TCI of remifentanil with continuous pumping dexmedetomidine can effectively inhibit the stress response to fibreoptic bronchoscopy in patients with severe tracheal stenosis while maintaining spontaneous breathing. Under the anesthesia management of an experienced anesthesiologist, it provides a reference to tracheoscopic anesthesia of autonomous breathing.